SEMANGAT KERJA SEBAGAI MEDIASI: MOTIVASI KERJA DAN KEPUASAN KERJA KOMITMEN PEGAWAI DINAS PARIWISATA KOTA BATU - Ika Fatma Yulia Winda Jayanti; Rahayu Puji Suci; Arief Purwanto (IAIN Batusangkar, 2021)
Empirical evidence obtained from this study is that increased work motivation can increase employee commitment and better job satisfaction and increase employee commitment, either partially or simultaneously. The wording spirit can mediate so that work motivation and job satisfaction can increase the responsibility of the Batu City Tourism Office employees. This result is supported by descriptive statistics, which mean moderate to high